Reactivation of intrabasement structures during rifting: a case study from offshore southern Norway - Phillips,T; Jackson,CA-L; Bell,RE; Duffy,OD; Fossen,H (Journal of Structural Geology, 2016)
Pre-existing structures within crystalline basement may exert a significant influence over the evolution of rifts. However, the exact manner in which these structures reactivate and thus their degree of influence over the overlying rift is poorly understood. Using borehole-constrained 2D and 3D seismic reflection data from offshore Southern Norway we identify and constrain the three-dimensional geometry of a series of enigmatic intrabasement reflections. Through 1D waveform modelling and 3D mapping of these reflection packages, we correlate them to the onshore Caledonian thrust belt and Devonian shear zones. Based on the seismic-stratigraphic architecture of the post-basement succession we identify several phases of reactivation of the intrabasement structures associated with multiple tectonicevents. Reactivation preferentially occurs along relatively thick (c. 1km), relatively steeply dipping (c. 30°) structures, with three main styles of interactions observed between them and overlying faults: (i) faults exploiting intrabasement weaknesses represented by intra-shear zone mylonites; (ii) faults that initiate within the hangingwall of the shear zones, inheriting their orientation and merging with said structure at depth; or (iii) faults that initiate independently from and cross-cut intrabasement structures. We demonstrate that large-scale discrete shear zones act as a long-lived structural template for fault initiation during multiple phases of rifting.